Evaluation of Chlorogenic Acid in Flos lonicerae by HPLC Method - Weiping, Liao; Yukui, Rui (Asian Journal of Chemistry, 2010)
High-performance liquid chromatography has been evaluated for the determination of chlorogenic acid in Flos lonicerae, primarily by the separation of chlorogenic acid. The samples were extracted at reflux by methanol and the content of chlorogenic acid was analyzed by HPLC. A diamonsil C18 column (4.6 mm × 150 mm, 5 μm) was used as the analytical column. The mobile phase was methanol, water and phosphoric acid (20:80:0.1). The detection wavelength was set at 327 nm to determine the content of chlorogenic acid. The chlorogenic acid showed linearity over the range of 8.8-88 μg/mL (r = 0.9999). Its average recovery rate was 98.1 % and RSD was 1.85 % (n = 5). The accuracy of the method was 0.82 % (n = 5).